2019
DOI: 10.3390/jcm9010116
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-8 (GDF8)/Myostatin Is a Predictor of Troponin I Peak and a Marker of Clinical Severity after Acute Myocardial Infarction

Abstract: Objective: Growth differentiation factor-8 (GDF8), also known as myostatin, is a member of the transforming growth factor-β superfamily that inhibits skeletal muscle growth. We aimed to investigate the association between GDF8 and peak troponin I levels after acute myocardial infarction (AMI). Methods: All consecutive patients admitted from June 2016 to February 2018 for type 1 AMI in the Coronary Care Unit of University Hospital of Dijon Bourgogne (France) were included in our prospective study. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The same study demonstrated that high circulating myostatin is a risk factor of chronic HF rehospitalization and an independent predictor of mortality. Myostatin was also found to correlate with troponin I peak in patients with acute myocardial infarction, possibly reflecting the extent of damage to the myocardium [ 168 ]. Research on patients referred for phase II cardiac rehabilitation indicated no influence of such procedure on serum myostatin level; however, patients with congestive HF were excluded from this study, highlighting the necessity of examining the effect of cardiac rehabilitation on circulating myostatin levels in HF [ 169 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…The same study demonstrated that high circulating myostatin is a risk factor of chronic HF rehospitalization and an independent predictor of mortality. Myostatin was also found to correlate with troponin I peak in patients with acute myocardial infarction, possibly reflecting the extent of damage to the myocardium [ 168 ]. Research on patients referred for phase II cardiac rehabilitation indicated no influence of such procedure on serum myostatin level; however, patients with congestive HF were excluded from this study, highlighting the necessity of examining the effect of cardiac rehabilitation on circulating myostatin levels in HF [ 169 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…As elevated expression of COX-2 in cardiomyocytes has been associated with heart failure ( Abbate et al, 2004 ), the lack of significant effects on COX-2 expression corroborates the evidence of reduced cardiac toxicity, even after I/R injury, in D -tagatose diet when compared to fructose feeding. The significant difference in expression levels of hydroxyproline, whose measurements accurately reflect the amount of collagen in the tissue, and GDF8, a reliable marker of clinical severity after acute myocardial infarction ( Meloux et al, 2019 ), which were both maximally upregulated in the I/R heart of fructose-fed rats and only slightly overexpressed in the presence of D -tagatose, is a further evidence of the limited toxic impact of D -tagatose diet on cardiac damage after I/R when compared to a fructose rich diet.…”
Section: Discussionmentioning
confidence: 99%
“…GDF8/MSTN has broad physiological roles in different tissues, including most significantly as an inhibitor of skeletal muscle growth ( McPherron et al, 1997 ), and as a regulator of fibrosis of the heart ( Morissette et al, 2009 ) and mineral density in the bone ( Suh et al, 2020 ). Although GDF8/MSTN is primarily found in skeletal muscle, both fetal and adult hearts express the gene at a low level, and its circulation level is induced following myocardial infarcts ( Castillero et al, 2015 ; Meloux et al, 2019 ) and heart failure ( George et al, 2010 ). Critically, selective deletion of Gdf8/Mstn in the heart is sufficient to prevent muscle loss in mouse models of heart failure ( Heineke et al, 2010 ), thus suggesting the circulating pool of GDF8/MSTN contributed by the heart functions to regulate the mass of skeletal muscles in an endocrine fashion.…”
Section: Definition Of Cardiokinesmentioning
confidence: 99%